The existence of Rimpu Culture in Bima, West Nusa Tenggara, Indonesia - Fitriyanti, Fitriyanti (Enigma Institute, 2023)
The Bima people are known for their distinctive style of clothing, known as Rimpu culture. The Bima culture of Rimpu, which involves covering one's privates, especially for adult women, is an expression of religious ideals. This review attempts to explain West Nusa Tenggara's Bima district's Rimpu culture. Those who wear the traditional Bima sarong are known as Rimpu wearers. A set of clothes known as rimpu makes use of two sarongs. After civilization emerged and Islam extended over Bima, there was a significant inflow of Rimpu people living there. One of the cultural systems in the West Nusa Tenggara region is the Rimpu culture. Local and national cultural leaders, religious authorities, and government representatives must actively maintain the Rimpu culture within the Bima community.